2021
DOI: 10.1002/celc.202100710
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Oxygen Reduction Reaction (ORR) on Pt Oxide Electrochemistry

Abstract: In this study, we employed microelectrodes and scanning electrochemical microscopy (SECM) to investigate the role of molecular oxygen and local pH changes on the electrochemistry of Pt oxide. We show that in acidic media and alkaline conditions, the impact of O2 is negligible, while in unbuffered neutral media, O2 strongly affects the formation of Pt oxides. Experiments carried under hindered diffusion reveal that this is due to a high local pH arising from the oxygen reduction reaction. This is evidenced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Considerable advances were made using bare Pt electrodes for local pH probing, [13b,16] based on the well‐known characteristics of polycrystalline Pt surfaces in acidic media. [ 17 ] However, the determination of the shift of the PtO Red reduction wave in the voltammogram is compromised if OER occurs at the sample electrode due to the high local oxygen partial pressure which leads to an overlapping voltammetric response due to the low‐overpotential oxygen reduction reaction (ORR) at the Pt probe [ 18 ] as depicted in Figure a. The convolution of the two processes, namely the potential overlap of PtO Red and ORR occurs over a wide pH range and therefore, Pt microelectrodes cannot be used in O 2 ‐generating reactions such as the OER for local pH determination.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable advances were made using bare Pt electrodes for local pH probing, [13b,16] based on the well‐known characteristics of polycrystalline Pt surfaces in acidic media. [ 17 ] However, the determination of the shift of the PtO Red reduction wave in the voltammogram is compromised if OER occurs at the sample electrode due to the high local oxygen partial pressure which leads to an overlapping voltammetric response due to the low‐overpotential oxygen reduction reaction (ORR) at the Pt probe [ 18 ] as depicted in Figure a. The convolution of the two processes, namely the potential overlap of PtO Red and ORR occurs over a wide pH range and therefore, Pt microelectrodes cannot be used in O 2 ‐generating reactions such as the OER for local pH determination.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the probe on electrochemical measurements was thoroughly investigated. These studies revealed meaningful insights regarding the hindering effect of the probe on the mass transport as well as local phenomena (e.g., local pH modification) due to the confinement of species between the probe and the substrate. However, this aspect is not explored for plasmon-driven photochemical reactions, during which the hot carrier extraction and the enhanced diffusion due to the thermal effect are mixed together. This increases the complexity of the underlying mechanisms driving the catalytic event.…”
mentioning
confidence: 99%